2022 American Society of Clinical Oncology (ASCO) Genitourinary Cancers Symposium: Meeting highlights - Kapoor, Anil; Niazi, Tamim; Noonan, Krista; Rendon, Ricardo A.; Alimohamed, Nimira; Kassouf, Wassim; Berlin, Alejandro; Chu, William; Kollmannsberger, Christian; So, Alan I. (Canadian Urological Association Journal, 2022)
The 2022 American Society of Clinical Oncology (ASCO) Genitourinary (GU) Cancers Symposium was held in San Francisco and online from February 17–19, 2022. Following the symposium, on February 22, the Canadian Urological Association (CUA) held an online webinar where Canadian experts highlighted key research findings in prostate, bladder, and kidney cancers. In this report, we summarize these exciting advances in GU oncology. The entire webinar can be viewed on the CUA website, and meeting abstracts can be viewed at the ASCO meeting library.